FORMACIÓN DE JÓVENES CIENTÍFICOS - Ishiyama Cervantes y Cols., Raúl (2019)
Constantly it is spoken of the importance of the scientific research for the development of the country. There is no uniformity in teaching to design the project, in the development of the investigation neither of the publication. In the Cayetano Heredia Peruvian University during 25 years the students of the first years learned to investigate in practical form. The lack of infrastructure, materials and equipment was not impediment. At the beginning of the course, I explain the importance of the investigation. They learned to use books and magazines for searching information on similar subjects. The methodology was simple as well as the design of the project and the presentation of the result of the investigation. To write the report they counted on “Steps for publishing the thesis”. By the end of the semester, the students exposed their works to their companions in similar form as the scientific congresses. The objective was to attract them towards the investigation, in practical and entertained form that gave to them personal satisfactions. This experience is to disposition of the interested ones.